2005
DOI: 10.1097/01.olq.0000175414.80023.59
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effectiveness Analysis of Interventions to Increase Repeat Testing in Patients Treated for Gonorrhea or Chlamydia at Public Sexually Transmitted Disease Clinics

Abstract: Phone reminders are more cost-effective than motivational counseling and improve return rates over a brief recommendation given at the time of initial treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…17 In contrast, a pilot study in New York of incentives and mail or telephone reminders found no substantial increase in return rates. 26 Though telephone reminders have been found to be the most effective intervention in increasing patient return rates and the least costly in terms of cost per infection treated, 27 our data demonstrate that only 29% of family planning providers report using phone reminders for retesting visits.…”
Section: Discussioncontrasting
confidence: 55%
“…17 In contrast, a pilot study in New York of incentives and mail or telephone reminders found no substantial increase in return rates. 26 Though telephone reminders have been found to be the most effective intervention in increasing patient return rates and the least costly in terms of cost per infection treated, 27 our data demonstrate that only 29% of family planning providers report using phone reminders for retesting visits.…”
Section: Discussioncontrasting
confidence: 55%
“…One study assessed cost-effectiveness of phone call reminders and found brief verbal advice combined with a phone reminder yielded the highest return rate and the lowest cost per infection treated compared with brief verbal advice alone or a financial incentive 49. Other studies suggest that the use of SMS reminders is a cheap and effective way of increasing reattendance rates for HIV/STI testing, but no cost-effectiveness studies were performed.…”
Section: Discussionmentioning
confidence: 99%
“…However the optimum approach to repeat testing in England is yet to be established. The resources required and yield in terms of number of individuals having a repeat test are likely to vary according to the approach used (which might include recommendation by clinician at the time of treatment, telephone or text message reminders or posting home testing kits to consenting patients at an agreed interval) 16. Rates of repeat testing in countries that already recommend repeat testing following a positive test vary.…”
Section: Discussionmentioning
confidence: 99%